The frontal sinus- physiological and pathophysiological aspects- an endoscopist’s perspective: a review - Munjal, Manish; Puri, Sanjeev; Matta, Garima; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
In this era of minimally invasive surgical interventions, the knowledge of the physiology and pathophysiology of the frontal sinus is vital to the endoscopic rhinologist. The conventional procedure of sinus surgery has given way to functional endoscopic sinus surgery whereby now the emphasis is not on cleaning the sinus but reverting the function of the sinus. The surgery is only done at the frontal recess only. The physiology and pathophysiology of the frontal sinus needs an introspection.